(untitled) (Al-Qamar, 2023)
This study investigates the ongoing effect of the Rashidun Caliphs’ (Khulafa-e-Rashideen) leadership methods on contemporary Muslim monarchs. In Islamic philosophy, the leadership of the Rashidun Caliphs, particularly Abu Bakr, Umar ibn al-Khattab, Uthman ibn Affan, and Ali ibn Abi Talib, constituted an idealized type of government. Their concepts of consultation (Shura), fairness (Adl), stewardship (Khilafa), Quranic teaching preservation, and social welfare have had a significant influence on modern Islamic governance. The notion of Shura is profoundly established in current Islamic constitutions, supporting collective decision-making and shared responsibility, according to this study. The devotion to Adl is reflected in contemporary Islamic legal systems, which promote fairness, equity, and accountability, including Zakat collecting and distribution methods. The Khilafa idea may be seen in the leadership styles of many current Muslim leaders who prioritize the welfare and development of their constituency. Furthermore, the emphasis on maintaining and spreading Quranic teachings during the Rashidun era is mirrored today in the emphasis on Islamic education and Quranic literacy in Muslim-majority countries. The ongoing relevance and influence of the Rashidun Caliphs’ leadership styles provide useful insights for contemporary Muslim rulers, demonstrating the eternal importance of these ideals in directing Muslim-majority states despite modern world challenges.